The write start : a guide to nurturing writing at every stage, from scribbling to forming letters and writing stories - Hallissy, Jennifer (Trumpeter Books, 2010)
How do you raise children who love to write? Jennifer Hallissy believes that if you give children a solid foundation of writing basics, they will develop a love of writing that lasts a lifetime. In this book, she shares the secrets for supporting young writers, from the smallest of scribblers to middle-schoolers mastering script. You are your child's first writing teacher, and their most important writing role model. From teaching your child how to hold a pencil and form the letters of the alphabet, to creating writing spaces and meaningful writing rituals at home, this book gives you all of the information and inspiration you need to raise a confident writer.